Analisis Pengambilan Keputusan Pembelian Fashion Involvement terhadap Impulse Buying di Masa Pandemi - Acep Samsudin; Rusdi Hidayat; Shinta Kezia Apriliani; Bebyzanna Bella Faumara; Anindya Sekar Purnomo; Nabilla Rahma Maharsany (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
This study aims to determine the influence of Fashion involvement in buying decisions on Impulse Buying Through the Positive Emotions of Teenagers during the Covid-19 pandemic. In making this journal using the method of literature study. In compiling this journal, the author uses various journals with the discussion of each journal still related to being a reference material in making this journal. The results of the study show that fashion involvement and positive emotion have an impact on impulse buying. This means that fashion involvement has a positive influence on impulse buying behavior with fashion involvement playing an important role because it has an impact on consumer decisions and positive emotion also has a positive influence on customer desires to make unplanned purchases, so that it has a big impact on consumer desires to make impulse buying. Keywords: Fashion involvement, positive emotion, impulse buying.